The first serological detection and risk factors analysis of Rift Valley fever virus in sheep and goats in Fars province, southern Iran - Mohsen Manavian; Majid Hashemi; Mehran Bakhshesh; Farhang Tavan; Mahnaz Samsami; Fatemeh Saemi (Journal of Zoonotic Diseases)
Rift Valley fever is a vector-borne zoonosis that can affect various species, including ruminants and camels. The present study reports the first serological detection of the Rift Valley fever virus in sheep and goats, along with an analysis of risk factors in Fars province, located in the south of Iran. The province of Fars was distributed into three climate zones, and three cities were accidentally chosen for each climatic zone. Two epidemiologic units were selected in each city, and samples of all the sheep and goats were collected from each unit. In total, 540 serum samples (391 from sheep and 149 from goats) were gathered and tested by a commercial ELISA kit. Out of 540 samples tested, 12 (2.2%) were found to be seropositive for the Rift Valley fever virus, with 10 from sheep and 2 from goats, indicating the presence of specific antibodies. The correlation between seropositivity and risk factors such as age, sex, climate, animal type, and, history of abortion was not significant. In conclusion, the Rift Valley fever virus is not endemic in Fars province. Further studies are recommended to investigate the distribution of mosquito vectors and their genotype in Fars province, isolate the virus, and develop vaccines.